UNIVERSITAS INDONESIA SYSTEM SUPPORT IN ACCELERATING LECTURERS TO IMPLEMENT ODEL FACILITIES - T. Ahmad Danial; Irma Septuriany Dewanti; Dimas Septian Saputra (Journal of Research and Innovation In Open and Distance Learning, 2023)
Directorate of Academic Advancement and Learning Resources Universitas Indonesia (DPASDP UI) established in 2020 and one of sub-directorate "Learning Resources" main role is to support learning activities in UI by managing learning facilities such as learning management system (EMAS), computer laboratory, video conference room, and production house. The covid-19 pandemic forced all learning to be held at a distance and fully online, which was only 20% of courses using LMS before the pandemic. Thousands of classes need to be opened in EMAS, so non-eLearning teachers face confusing situations. Several support-system efforts have been opened and revitalized, such as providing migrate-to-online learning guidelines, organizing more teacher training, upgrading the LMS, and establishing a fully online helpdesk. Moreover, the UI strategic plan year 2022 revision has mandated UI to be more implementing technology and increase the number of MOOCs opened, so more facilities development is certainly needed. This paper elaborates on UI strategies and lesson-learned in facing the situations and some effort to keep relevant.